Reactivity of hypervalent iodine(III) reagents bearing a benzylamine with sulfenate salts - Dedeiras, Beatriz; Caldeira, Catarina S.; Cunha, José C.; Gomes, Clara S. B.; Marques, M. Manuel B. (Beilstein Journal of Organic Chemistry, 2024)
The reactivity of our recently disclosed hypervalent iodine reagents (HIRs) bearing a benzylamine with in situ-generated sulfenate salts was investigated. Under the studied conditions sulfonamides have been obtained in up to 52% yield. This reaction has been extended to a variety of HIRs and sulfenate salts to explore the different reactivity of these new reagents. A plausible mechanism is proposed, suggesting a possible radical pathway.
Keywords: electrophilic amination; hypervalent iodine reagents; sulfinamide; sulfonamide